2002
DOI: 10.1096/fj.02-0183fje
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of IGF‐1 Transgene to Skeletal Muscle Accelerates Muscle and Motor Neuron Regeneration

Abstract: Currently, there is no known medical treatment that hastens the repair of damaged nerve and muscle. Using IGF-1 transgenic mice that specifically express human recombinant IGF-1 in skeletal muscle, we test the hypotheses that targeted gene expression of IGF-1 in skeletal muscle enhances motor nerve regeneration after a nerve crush injury. The IGF-1 transgene affects the initiation of the muscle repair process after nerve injury as shown by increased activation of SCA-1positive myogenic stem cells. Increased sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 55 publications
1
84
0
8
Order By: Relevance
“…Although it has been demonstrated that increased IGF-I levels improve skeletal muscle regeneration after various types of injuries, no study had compared the relative efficacy of various methods of IGF-I delivery to enhance functional recovery. 17,18,[20][21][22] Our findings indicate that IGF-I hastens functional recovery after myotoxic injury, regardless of the route of administration, but that electrotransfer-assisted Figure 4 Mean data for tetanic force production of the TA muscle measured in situ at 7, 14, 21 or 28 days after notexin-induced injury. Four days after myotoxic injury, the TA was injected with 80 mg of a plasmid encoding IGF-I followed by electrotransfer (pIGF-I).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although it has been demonstrated that increased IGF-I levels improve skeletal muscle regeneration after various types of injuries, no study had compared the relative efficacy of various methods of IGF-I delivery to enhance functional recovery. 17,18,[20][21][22] Our findings indicate that IGF-I hastens functional recovery after myotoxic injury, regardless of the route of administration, but that electrotransfer-assisted Figure 4 Mean data for tetanic force production of the TA muscle measured in situ at 7, 14, 21 or 28 days after notexin-induced injury. Four days after myotoxic injury, the TA was injected with 80 mg of a plasmid encoding IGF-I followed by electrotransfer (pIGF-I).…”
Section: Discussionmentioning
confidence: 83%
“…Studies on transgenic mice have shown that IGF-I overexpression prevents an age-related decrease in skeletal muscle mass and regenerative capacity and that IGF-I enhances skeletal muscle regeneration after myotoxic injury or nerve damage. [15][16][17] Viral-mediated IGF-I delivery prevents the age-related loss of skeletal muscle function and has been shown to promote skeletal muscle hypertrophy in an additive manner when combined with resistance exercise training. 18,19 Non-viral plasmid-based electroporationassisted IGF-I gene transfer has been shown to enhance skeletal muscle regeneration after laceration injury.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, musclespecific over-expression of IGF-1 has been shown to ameliorate the dystrophic phenotype in the MDX mouse (an animal model for Duchenne muscular dystrophy) [28], and has been shown to accelerate muscle regeneration [29]. IGF-1 binding, which can be modulated via the effects of IGF binding proteins, activates the IGF-1 receptor (IGFR), a receptor tyrosine kinase.…”
Section: Heart Failure and Angiotensin IImentioning
confidence: 99%
“…Among the numerous growth factors involved at the onset of the regeneration process, IGF-I is known to stimulate satellite cell proliferation and differentiation and to increase muscle protein synthesis (16,41). IGF-I activates the phosphatidylinositol 3-kinase (PI3K)-protein kinase B (Akt) pathway, which is necessary and sufficient to induce skeletal muscle hypertrophy (20).…”
mentioning
confidence: 99%